Percepción del adulto mayor hospitalizado sobre el cuidado de enfermería - Alvarado Tapia, María Teresa (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
Aging, unavoidable and gradual phenomenon that increase users population of health services and number of complaints too about their attention, without specify if is responsible nursing. The objective was to analyze the perception to older adults hospitalized about nursing’s care in the internal medicine and nephrology services inside of General Hospital “Vasco de Quiroga” of ISSSTE. Precedents: Used it the Theory disciplinary about carefully humanized of Transpersonal Human Caring of Dra. Watson, which humanist focus maintain relation with this research work from moral and ethics values that patient perceive it. Justification: The no existence a record about the perception of older adults hospitalized about nursing’s care, arouse the present investigation; Watson’s care describe it like a mental process where there are significant moments among patient and nurse. Methodology: Is a quantitative, cross-sectional and descriptive study; universe no probabilistic and for convenience, 130 older adults hospitalized patients. Inclusion criterion: Older adults, between 65 and 80 years old than were long terms during the investigation period. Measuring instrument used: since then the operacionalisation of variables, made the “Perception of care of nursing” instrument, author’s whose is the responsible of this investigation, based in the instrument “Perception of care of nursing” (PCHE) from Rivera, Triana and Espitia, authors (2010).

El envejecimiento, fenómeno ineludible y gradual que incrementa la población usuaria de servicios de salud al unísono el número de quejas en torno a su atención, sin precisar si corresponden al profesional de enfermería. El objetivo fue analizar la percepción del adulto mayor hospitalizado sobre el cuidado de enfermería en los servicios de Medicina Interna y Nefrología del Hospital General “Vasco de Quiroga” del ISSSTE. Antecedentes: Se utilizó la teoría disciplinar del cuidado humanizado de la Dra. Watson sobre cuidado transpersonal, cuyo enfoque humanista mantiene relación con la presente investigación a partir de valores morales y éticos que el paciente percibe. Justificación: La falta de registros entorno a la percepción del adulto mayor hospitalizado sobre el cuidado de enfermería, suscitó el presente estudio; el cuidado Watson lo describe como proceso mental donde hay momentos significativos entre paciente y enfermera (o). Metodología: Es un estudio cuantitativo, transversal y descriptivo; muestreo no probabilístico y por conveniencia, 130 pacientes adultos mayores hospitalizados. Criterios de inclusión: Adultos mayores, entre 65 y 80 años que estuvieron internados durante el periodo de investigación. Instrumento utilizado: A partir de la Operacionalización de variables, se construyó el instrumento “Percepción del cuidado de Enfermería” cuya autora es la responsable de la presente investigación, basado en el instrumento “Percepción del cuidado humanizado de Enfermería” (PCHE) de los autores Rivera, Triana y Espitia (2010).
Facultad de Enfermería. Maestría en Enfermería
Keywords: info:eu-repo/classification/cti/3; FE-M-2015-1694; Enfermería geriátrica; Paciente; Satisfacción; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5624